Khotbah sebagai Karya Teologis: Meninjau Pentingnya Pengajaran Iman dalam Praksis Khotbah Masa Kini - Blegur, Romelus (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2025)
Preaching is an important means for the growth of the congregation's faith, because through it the word of God is proclaimed. Based on that, the preaching service must be actualized properly as a forum for serving the word of God. The challenge of today's sermons is the emergence of sermons that arouse the psychology of the listener and are full of humanist messages without theological depth. Such sermons tend to be entertaining and do not prepare the faith of the congregation and believers to face today's doctrinal challenges. This problem must be addressed by returning the sermon to its substance. One important offer to address this problem is to make sermons a theological work in which the Christian faith can be taught. The method used in this research is the library method through literary sources, both books and scientific journal articles. The results of this research are, first. Preaching is an important service that supports the existence of the church because through it the word of God is preached and builds the faith of the congregation. Second, the challenge of contemporary preaching that deviates from its objectives is a reality that cannot be ignored, therefore it must be addressed. Third, the sermon should be a theological work, because through it Christian doctrines are taught as a solid foundation for the congregation's faith both cognitively and practically in facing today's challenges.